Global mapping of rat plasma proteins with a native proteomic approach using nondenaturing micro 2DE and quantitative LC‐MS/MS. Issue 23 (31st October 2016) - Chen, Shumin; Wen, Meiling; Bu, Shujie; Wang, Ahui; Jin, Ya; Tan, Wen
Abstract : Plasma samples from adult male rats were separated by nondenaturing micro 2DE and a reference gel was selected, on which 136 CBB‐stained spots were numbered and subjected to in‐gel digestion and quantitative LC‐MS/MS. The analysis provided the assignment of 1–25 (average eight) non‐redundant proteins in each spot and totally 199 proteins were assigned in the 136 spots. About 40% of the proteins were detected in more than one spot and 15% in more than ten spots. We speculate this complexity arose from multiple causes, including protein heterogeneity, overlapping of protein locations and formation of protein complexes. Consequently, such results could not be appropriately presented as a conventional 2DE map, i.e. a list or a gel pattern with one or a few proteins annotated to each spot. Therefore, the LC‐MS/MS quantity data was used to reconstruct the gel distribution of each protein and a library containing 199 native protein maps was established for rat plasma. Since proteins that formed a complex would migrate together during the nondenaturing 2DE and thus show similar gel distributions, correlation analysis was attempted for similarity comparison between the maps. The protein pairs showing high correlation coefficients included some well‐known complexes, suggesting the promising application of native protein mapping for interaction analysis. With the importance of rat as the most commonly used laboratory animal in biomedical research, we expect this work would facilitate relevant studies by providing not only a reference library of rat plasma protein maps but a means for functional and interaction analysis.